2017
DOI: 10.5664/jcsm.6564
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy Using a Mobile Application Synchronizable With Wearable Devices for Insomnia Treatment: A Pilot Study

Abstract: Study Objectives: The use of telemedicine with a mobile application (MA) and a wearable device (WD) for the management of sleep disorders has recently received considerable attention. We designed an MA synchronizable with a WD for insomnia treatment. Our pilot study determined the efficacy of simplified group cognitive behavioral therapy for insomnia (CBT-I) delivered using our MA and assessed participant adherence to and satisfaction with the device. Methods: The efficacy of the CBT-I using MA (CBT-I-MA) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…The researchers found that those who used mobile apps and stress algorithm were more likely to complete their goals and demonstrated reduced stress and anger compared with the control group. It can be inferred from the results that the SMSR integrated with CBT and the SRL strategy helped enhance users’ cognition of sleep hygiene; this finding is consistent with that reported in another study [ 33 ], showing that CBT integrated with mobile apps would be a positive treatment for patients with insomnia. On the other hand, this study also found that users could gain benefits by using the SRL strategy integrated with a mobile app, no matter whether they were using wearable devices or not; this implies that the guidance provided in the self-monitoring process could help users be aware of their own situations and, hence, improve their sleep quality.…”
Section: Discussionsupporting
confidence: 89%
“…The researchers found that those who used mobile apps and stress algorithm were more likely to complete their goals and demonstrated reduced stress and anger compared with the control group. It can be inferred from the results that the SMSR integrated with CBT and the SRL strategy helped enhance users’ cognition of sleep hygiene; this finding is consistent with that reported in another study [ 33 ], showing that CBT integrated with mobile apps would be a positive treatment for patients with insomnia. On the other hand, this study also found that users could gain benefits by using the SRL strategy integrated with a mobile app, no matter whether they were using wearable devices or not; this implies that the guidance provided in the self-monitoring process could help users be aware of their own situations and, hence, improve their sleep quality.…”
Section: Discussionsupporting
confidence: 89%
“…There were two studies that focused on both physical activity and sleep, one in an employee wellness program, [53] one in college students [56]. One study reported on a pilot study of CBT for insomnia using a mobile application paired with a wearable device [54]. The results of the intervention studies were variable.…”
Section: Resultsmentioning
confidence: 99%
“…CBT-I coach is a central place to track sleep habits, provide tools (e.g., relaxation breathing, guided imagery), and encourage positive reinforcement. 8 As insomnia is multifactorial, appropriate management of comorbid medical illness should be emphasized. In particular, obstructive sleep apnea, pain disorders, mood disorders, substance use disorders, and nocturia should all be treated effectively.…”
Section: Nonpharmacologic Treatmentmentioning
confidence: 99%